Proton-modulated interactions of ions with transport sites of prokaryotic and eukaryotic NCX prototypes. (November 2021) - Refaeli, Bosmat; Liu, Stephanie; Hiller, Reuben; Giladi, Moshe; Baiz, Carlos R.; Khananshvili, Daniel
Highlights: The cytosolic pH decrease from 7.2 to 6.9 results in nearly 90% inactivation ("proton block") of mammalian NCXs involving proton interactions with transport and regulatory domains. In contrast with prokaryotic NCXs, protons gradually modulate the transport sites of mammalian NCXs in a wide range of pH, thereby shifting the carboxylate deprotonation to the alkaline range. Replacement of single ion-coordinating residue (T50S) in the prokaryotic NCX_Mj can "recapitulate" the pH-dependent profiles possessed by transport sites of eukaryotic NCX. Specific structural elements of transport domain in mammalian (but not in prokaryotic) NCXs, may contribute to "proton block" and may undergo a secondary amplification by allosteric modes. Abstract: The cytosolic pH decline from 7.2 to 6.9 results in 90% inactivation of mammalian Na + /Ca 2+ exchangers (NCXs) due to protons interactions with regulatory and transport domains ("proton block"). Remarkably, the pH titration curves of mammalian and prokaryotic NCXs significantly differ, even after excluding the allosteric effects through regulatory domains. This is fascinating since "only" three (out of twelve) ion-coordinating residues (T50S, E213D, and D240N) differ between the archaeal NCX_Mj and mammalian NCXs although they contain either three or two carboxylates, respectively. To resolve the underlying mechanisms of pH-dependent regulation, the ion-coordinating residues of NCX_Mj were mutated to imitate the ion ligation arrays of mammalian NCXs; the mutational effects were tested on the ion binding/transport by using ion-flux assays and two-dimensional infrared (2D IR) spectroscopy. Our analyses revealed that two deprotonated carboxylates ligate 3Na + or 1Ca 2+ in NCX prototypes with three or two carboxylates. The Na + /Ca 2+ exchange rates of NCX_Mj reach saturation at pH 5.0, whereas the Na + /Ca 2+ exchange rates of the cardiac NCX1.1 gradually increase even at alkaline pHs. The T50S replacement in NCX_Mj "recapitulates" the pH titration curves of mammalian NCX by instigating an alkaline shift. Proteolytic shaving of regulatory CBD domains activates NCX1.1, although the normalized pH-titration curves are comparable in trypsin treated and untreated NCX1.1. Thus, the T50S-dependent alkaline shift sets a dynamic range for "proton block" function at physiological pH, whereas the CBDs (and other regulatory modes) modulate incremental changes in the transport rates rather than affect the shape of pH dependent curves. Graphical abstract: Image, graphical abstract